Plan estratégico de marketing 2015- 2017 del comercial ag (franquicia disensa) de la ciudad de zumba, provincia de Zamora Chinchipe - Navarro Rodríguez, Victor Hugo (2015)
This research aims to know the current status of the Commercial AG (Franchise Disensa) Zumba city, using for this purpose, some means such as: market research, situation analysis, SWOT matrix, among others, elements They provide the basis for building the proposed marketing plan for the company. 1. Conduct market research to identify current or future problems that may affect the Commercial AG, through inquiry of marketing variables such as:: target, competition, market products to meet this purpose the following objectives , pricing, promotion, distribution, analysis of strengths, weaknesses, opportunities and threats, etc. and 2. Ask a proposed marketing plan based on the market investigation, it basically contain: objectives, strategies, operational plans, budgets, among others. For the development of the research was based on the analysis of the current situation of the Trade AG; in the case of internal analysis an interview was applied to the manager and employee survey, information which identified strengths and weaknesses of the company, for external analysis, a survey was applied to customers and members of the competition, information used to identify opportunities and threats, then the SWOT matrix is built, then proceeded to determine the key success factors, strategies and tactics, operational programs, the overall schedule, the budget and the plan was constructed to verify whether activities they are complying properly depending on the objectives. After done the research process was reached the following findings and conclusions, among which we can mention: - Comercial AG Zumba city has been run without strategic direction defined in a plan, which has not allowed it to position itself in a better way in the sector of influence. - Employees of the company are not trained regularly, resulting in dissatisfaction and churn to competition, poor management of processes, among others. - In the analysis of macro and microenvironment is identified that the trend of growth in the construction sector (Annex 7) at the national level will be maintained despite the current economic crisis, this because the government keeps momentum to this sector, manifested for example in the reduction of interest rates on loans for the builder and the purchaser of the houses, the impulse to the construction of road infrastructure, health and other remains. - The trading company AG has a very important feature is that the franchisee be obtained from its suppliers differentiation in prices and in turn excellent quality of products, which is reflected in its best competitive advantage (See Competitive Profile Matrix). - The company does not use any advertising medium to promote a better way its products. - The company does not have all products needed by the sector, so it is essential that the emphasis in the area of research and business development, enabling it to diversify its offer.